THE PREVALENCE OF KIDNEY FAILURE DUE TO URINARY CALCULI IN THE UROLOGY INPATIENT CARE DR. SOETOMO HOSPITAL FROM JANUARY 2016 TO DECEMBER 2017 - Bima Satriyastyo; Tarmono Djojodimedjo; Anny Setijo Rahaju (Jurnal Urologi Indonesia, 2022)
Objective: To know the profile of patients with kidney failure due to urinary calculi in the Urology Inpatient Care Soetomo General Hospital from January 2016 to December 2017. Material & Methods: a retrospective descriptive study was performed among 35 patients with kidney failure due to urinary tract stones. Individual patient data were obtained from the medical record. Results: The sex ratio known from the study between men and women was 60% : 40%. The age distribution was dominated by the patient within the range of 41-50 years old (38.14%) then followed by 51-60 and 31-70 years old (28.58% each), least found on <40 and >70 years old patient (2.86% each). Most of the urinary calculi were found in kidney (55.56%) then ureter (40%), and least found on urethra and bladder (2.22% each). Most types of renal failure found were Chronic Kidney Disease (48.57%), then Acute Kidney Injury (40%) then Acute Chronic Kidney Disease (11.43%). Conclusion: Chronic Kidney Disease was the most common type of renal failure found in the study compared to the other types such as Acute Kidney Injury and Acute on Chronic Kidney Disease. Calculus of kidney was the most frequent urinary calculi found. Men are more at risk of having kidney failure due to urinary calculi. 41-50 years old patients were found the most in this study.